Statistical Modelling of Ultrasonic-Aided Extraction of Elaeis guineensis Leaves for Better-Quality Yield and Total Phenolic Content - Nissha Bharrathi Romes; Mariani Abdul Hamid; Siti Ernieyanti Hashim; Roswanira Abdul Wahab (Universitas Gadjah Mada, 2019)
The present study highlighted the statistical modeling of an ultrasonic-aided extraction (UAE) of Elaeis guineensis leaves extract for maximal extraction yield (EY) and total phenolic content (TPC). A Box-Behnken design investigated the effects of ethanol concentration (X1: 0−100%), extraction time (X2: 5−55 min), the solvent-to-solid ratio (X3: 15:1−35:1 mL/g) and sonification amplitude (X4: 20−100 %). Under optimized conditions, the highest EY of 14.38% was attained using 50% (v/v) ethanol:water ratio, 55 min, 35 mL/g solvent-to-solid ratio, 60% sonication amplitude, whereas maximum TPC was 209.70 mg gallic acid equivalent (GAE)/g [50% (v/v) ethanol:water ratio, 30 min, 25 mL/g solvent-to-solid ratio, 60% sonication amplitude]. Second-order polynomial models of EY and TPC showed the R2 value corresponding to 0.9303 and 0.9500, respectively, indicating their significance (p < 0.05) to predict the responses. HPLC chromatograms revealed gallic acid and catechin were present in the UAE extracts. UAE technique afforded better EY (14.38%) and TPC (209.70 mg GAE/g) than maceration (3.73%, 85.23 mg GAE/g) and Soxhlet (6.86%, 102.13 mg GAE/g) extractions, as based on scanning electron micrographs of untreated, UAE, macerated and Soxhlet treated samples. Cell walls of ultrasonic-treated E. guineensis leaves were visibly disrupted to facilitate the higher release of bioactive plant materials, thus justifying the higher EY and TPC. The application of ultrasound appeared to remarkably increase the extraction efficiency of E. guineensis leaves to extract as compared to the conventional methods.